2015
DOI: 10.1186/s12967-015-0746-z
|View full text |Cite
|
Sign up to set email alerts
|

Milk: an epigenetic amplifier of FTO-mediated transcription? Implications for Western diseases

Abstract: Single-nucleotide polymorphisms within intron 1 of the FTO (fat mass and obesity-associated) gene are associated with enhanced FTO expression, increased body weight, obesity and type 2 diabetes mellitus (T2DM). The N6-methyladenosine (m6A) demethylase FTO plays a pivotal regulatory role for postnatal growth and energy expenditure. The purpose of this review is to provide translational evidence that links milk signaling with FTO-activated transcription of the milk recipient. FTO-dependent demethylation of m6A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 348 publications
(397 reference statements)
2
52
0
3
Order By: Relevance
“…We cannot conclude that FTO is responsible for PCa development at early age in PR, but the poor dietary patterns in this population [29,34,55] may influence the FTO effect on obesity and hence in PCa. Studies in other populations with a high European heritage had suggested that consumption of animal protein, milk and dairy protein might increase the PCa risk by hormonal changes [17,56]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We cannot conclude that FTO is responsible for PCa development at early age in PR, but the poor dietary patterns in this population [29,34,55] may influence the FTO effect on obesity and hence in PCa. Studies in other populations with a high European heritage had suggested that consumption of animal protein, milk and dairy protein might increase the PCa risk by hormonal changes [17,56]. …”
Section: Discussionmentioning
confidence: 99%
“…Milk contains high concentrations of miRNA-29s rich exosomes, which attack DNA methyltransferases, reducing the methylation of FTO CpG islands, stimulating FTO expression [17]. Moreover, in animal model’s overexpression of FTO increases the expression of the RUNX1T1 transcription factor in embryonic fibroblasts stimulating the number of adipocytes [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same way as for other biological fluids, the detection of microRNAs in milk from various species (Melnik, 2015a;Melnik & Schmitz, 2017a) opened the way for prognostic, diagnostic, and functional studies on milk microRNAs (Cui, Zhou, Ross, & Zempleni, 2017;Zempleni et al, 2016), especially because milk is the biological fluid that contains the highest level of microRNAs relative to its volume (Weber et al, 2010).…”
Section: Micrornas In Milkmentioning
confidence: 99%